ANALISIS RESPONS SISWA TERHADAP PENGGUNAAN METODE BRAINSTORMING DALAM PEMBELAJARAN MENULIS TEKS DRAMA - Eka Mulyasari; Wikanengsih; Alfa Mitri Suhara (IKIP Siliwangi, 2023)
The background this research is based on fun learning that will be seen from students during the learning process. It is supported by the use of learning methods that can make students active in learning. This research is a descriptive study that aims to describe analyze the response of students to the use of brainstorming method in learning drama text. The method in this study uses descriptive qualitative. The instrument used is a questionnaire containing 20 statement items. There are five indicators with ten positive statements and ten negative statements. The sample in this study was obtained from class VIII students at Bhakti Mulya Junior High School totaling 30 people. The results of the research on the indicator of the ease of students in understanding the material obtained an average percentage of 72.64%, the indicator of student learning methods obtained an average percentage of 78.43%, the indicator of learning methods making students active in learning obtained an average percentage of 74.63%, the indicator of students writing skills obtained an average percentage of 73%, the indicator of the usefulness felt by students obtained an average percentage of 77.37%. Based on these five indicators, an average score of 75.2% was obtained, indicating that students responses to the use of brainstorming methods in text learning were categorized as strong in each indicator. Students feel the benefits of using the brainstorming method in learning drama texts so that it makes it easier for students to understand the material, motivates students, students are active in the learning process and skilled in writing.